A quantitative analysis of the performance of the Windward Islands Banana Industry : measuring total factr productivity growth, 1965-1995 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This document explains on bananas are the most important tropical fruit in world trade. In, 1995, world imports of bananas totaled 10.6 million metric tons valued at over US .3 billion. The Windward islands have traditionally depended significantly on banana export earnings. Though per capit banana imports have risen over the last 10 years, real prices have generally declined. As the growth and revenue prospects for banana exports are not anticipated to improve, countries have intensified to improve, countries their efforts to improve the viability of banana cultivation or to find some alternative economic activity.